SPECIFIC FEATURES OF THE TECHNOLOGY OF USING MIXED REINFORCED CONCRETE FLOORINGS IN THE CONSTRUCTION OF MULTI-STORY RESIDENTIAL BUILDINGS - Abdurakhmanov Ulugbek Arabdjon ogli; Rasuljon Khamitov Khasanjon ogli (Western European Studies, 2025)
The technology of constructing cast reinforced concrete floors is currently one of the most promising. This advanced direction allows for the construction of multi-story residential buildings with a monolithic reinforced concrete frame with minimal labor and time expenditure, obtaining flexible architectural and planning solutions, which ensures the architectural appeal of buildings and the possibility of free planning of apartments. The technology of constructing cast reinforced concrete floors in the design of multi-story residential buildings provides the following possibilities:
Keywords: Cast reinforced concrete floor; Multi-story residential buildings; Heinze Cobiax International GmbH